Pesan Damai Al-Qur’an: Upaya Menumbuhkan Kesadaran Multikultural - Saifuddin , Saifuddin (LPPPM STAI Darul Hikmah Bangkalan, 2018)
This article is a library research in which the data is analyzed qualitatively.This writing focuses on the importance of multicultural education as an effort to keep the religious harmony as a representation of multicultural society. Multicultural education as the basis of education values cultural diversity. Whereas, the religious education is as a basis of education on religious values to produce religious men. The combination of these two concepts of education aims to make an educational system that integrates from both of them, or reduce the advantages, especially to produce religious humanist in a good character.